STRATEGI PENETAPAN HARGA DENGAN VARIASI HARGA DAN LABA USAHA TOKO BUAH DI KOTA BENGKULU - Clarita Tasya Mutiya Sari; Reflis Reflis; Hariz Eko Wibowo; Supriyadi Supriyadi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
This study aims to determine fruit prices and profit margins based on pricing strategies, examine price variations, and determine whether there are significant differences among pricing strategies in fruit shops in Bengkulu City. This study employed a quantitative survey of fruit stores in Bengkulu City, identified via Google Maps, using descriptive, profitability, price variability (CV), and statistical analyses. The results show that 61 types of fruit are sold, with imported fruit commanding higher prices than local fruit. Value-based pricing strategies yield the highest profit margins and sales revenue, although statistical tests indicate no significant differences among pricing strategies. The high CV value indicates that price variation is becoming increasingly heterogeneous. However, an increasing variety of fruits and high price variation do not necessarily correlate with increased revenue for the fruit store business. This study underscores the importance of value-based pricing strategies in enhancing profitability and customer loyalty.